Relationship between vitamin D status and antibody response to COVID-19 mRNA vaccination in healthy adults - Chillon, Thilo Samson; Demircan, Kamil; Heller, Raban; Hirschbil-Bremer, Ines Maria; Diegmann, Joachim; Bachmann, Manuel; Moghaddam-Alvandi, Arash; Schomburg, Lutz (Biomedicines, 2021)
The immune response to vaccination with SARS-CoV-2 vaccines varies greatly from person to person. In addition to age, there is evidence that certain micronutrients influence the immune system, particularly vitamin D. Here, we analysed SARS-CoV-2 IgG and neutralisation potency along with 25-hydroxy-cholecalciferol [25(OH)D] concentrations in a cohort of healthy German adults from the time of vaccination over 24 weeks. Contrary to our expectations, no significant differences were found in the dynamic increase or decrease of SARS-CoV-2 IgG as a function of the 25(OH)D status. Furthermore, the response to the first or second vaccination, the maximum SARS-CoV-2 IgG concentrations achieved, and the decline in SARS-CoV-2 IgG concentrations over time were not related to 25(OH)D status. We conclude that the vaccination response, measured as SARS-CoV-2 IgG concentration, does not depend on 25(OH)D status in healthy adults with moderate vitamin D status.
Gesehen am 18.10.2022